Identificação e análise dos processos de negócio de empresas de pequeno porte do setor da construção civil - Amarilla, Rosemara Santos Deniz (2013)
The present study has as objective to identify and analyze comparatively the main business processes of small companies of the subsector of edifications of the civil construction. Therefore, was used the qualitative research method and multiple case study as the main technique. Participated of this work, five companies that are located in the city of Curitiba, Paraná. For data collection were performed semi-structured interviews, document analysis and direct observations. From the information obtained, developed graphically mapping the business processes of each company using the BPMN notation. The study showed that the processes and activities of companies in this sector present common characteristics, thus facilitating the standardization of best practices. With the study of other cases will arise other similar aspects that could be used in the preparation of a reference model that provide specific guidance on how business processes can be managed in organizations of the subsector of edifications.